A 3D Carbon Foam Derived from Phenol Resin via CsCl Soft‐Templating Approach for High‐Performance Supercapacitor. Issue 3 (15th January 2020) - Yan, Tao; Wan, Ziyao; Wang, Kang; Hu, Maocong; Wang, Xitao
Abstract : Carbon with a 3D foam structure is synthesized by a one‐step strategy using low‐molecular‐weight phenolic resin as the precursor and CsCl as a salt template. Their electrochemical performance as electrodes is studied for symmetric supercapacitors. The distinct effect of CsCl addition amount on morphology, pore structure, electric conductivity, and electrochemical performance is further investigated. With appropriate CsCl addition amount, 3D carbon foam is harvested with abundant micropores and mesopores with a surface area beyond 1590 m 2  g −1 . It is tested as an electrode in a coin‐type symmetric supercapacitor with 6 m KOH and 1 m TEABF4 /MeCN as the electrolyte. The 3D carbon foam electrode displays specific capacitance of 259.3 F g −1 in 6 m KOH and 127.9 F g −1 in 1 m TEABF4 /MeCN at 0.5 A g −1 . Notably, it exhibits high energy density of 27.7 W h kg −1 in 1 m TEABF4 /MeCN. After 10 000 cycles, the specific capacitance remains at 96.9% in 6 m KOH, indicating good cycle stability. The superior performance of 3D carbon foam is attributed to larger surface area, higher electric conductivity, and unique 3D foam structure with sufficient 3D ion‐accessible channels. This work develops a simple, facile method to synthesize high‐performance supercapacitor electrode materials. Abstract : 3D carbon foam, with carbon nanorods as the skeleton crossed by graphene nanosheets, is harvested via carbonizing low‐molecular‐weight phenolic resin in the presence of a CsCl salt template. It possesses high specific surface area, abundant porous structure, and great electric conductivity, and exhibits superior electrochemical performance in a coin‐type symmetric supercapacitor in 6 m KOH and 1 m TEABF4 /MeCN.